Las preces hispánicas. Puesta al día y novedades - Anguita Jaén, José María; Fernández López, Mª Concepción (Exemplaria Classica, 2008)
The purpose of this paper is to update the status quaestionis of research into the Hispanic preces, a set of 180 rhythmic pieces characteristic of the old Hispanic liturgy, with a view to a future new critical edition. The paper focuses on the following topics: the manuscript tradition, the tradition within the liturgy, the circumstances of their composition, the question of their popular nature, the prosodic patterns and their survival in vernacular poetry, and the history of the pieces from their composition to their definitive inclusion in Ortiz’s Breviario. To conclude, the paper provides a sample of textual criticism on a passage corrupted in transmission.